Various Energetic Metabolism of Microglia in Response to Different Stimulations - Xiaohui Liu; Ning Jiang; Wenxia Zhou (Molecules, 2023)
The activation of the microglia plays an important role in the neuroinflammation induced by different stimulations associated with Alzheimer’s disease (AD). Different stimulations, such as pathogen-associated molecular patterns (PAMPs), damage-associated molecular patterns (DAMPs) and cytokines, trigger a consequence of activation in the microglia with diverse changes of the microglial cell type response in AD. The activation of the microglia is often accompanied by metabolic changes in response to PAMPs, DAMPs and cytokines in AD. Actually, we do not know the distinct differences on the energetic metabolism of microglia when subject to these stimuli. This research assessed the changes of the cell type response and energetic metabolism in mouse-derived immortalized cells (BV-2 cells) induced by a PAMP (LPS), DAMPs (Aβ and ATP) and a cytokine (IL-4) in mouse-derived immortalized cells (BV-2 cells) and whether the microglial cell type response was improved by targeting the metabolism. We uncovered that LPS, a proinflammatory stimulation of PAMPs, modified the morphology from irregular to fusiform, with stronger cell viability, fusion rates and phagocytosis in the microglia accompanied by a metabolic shift to the promotion of glycolysis and the inhibition of oxidative phosphorylation (OXPHOS). Aβ and ATP, which are two known kinds of DAMPs that trigger microglial sterile activation, induced the morphology from irregular to amoebic, and significantly decreased others in the microglia, accompanied by boosting or reducing both glycolysis and OXPHOS. Monotonous pathological changes and energetic metabolism of microglia were observed under IL-4 exposure. Further, the inhibition of glycolysis transformed the LPS-induced proinflammatory morphology and decreased the enhancement of LPS-induced cell viability, the fusion rate and phagocytosis. However, the promotion of glycolysis exerted a minimal effect on the changes of morphology, the fusion rate, cell viability and phagocytosis induced by ATP. Our study reveals that microglia induced diverse pathological changes accompanied by various changes in the energetic metabolism in response to PAMPs, DAMPs and cytokines, and it may be a potential application of targeting the cellular metabolism to interfere with the microglia-mediated pathological changes in AD.